2005
DOI: 10.1128/mcb.25.3.896-906.2005
|View full text |Cite
|
Sign up to set email alerts
|

Rejoining of DNA Double-Strand Breaks as a Function of Overhang Length

Abstract: The ends of spontaneously occurring double-strand breaks (DSBs) may contain various lengths of singlestranded DNA, blocking lesions, and gaps and flaps generated by end annealing. To investigate the processing of such structures, we developed an assay in which annealed oligonucleotides are ligated onto the ends of a linearized plasmid which is then transformed into Saccharomyces cerevisiae. Reconstitution of a marker occurs only when the oligonucleotides are incorporated and repair is in frame, permitting rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 42 publications
(50 reference statements)
6
97
0
Order By: Relevance
“…Oligonucleotide-modified Plasmids-OMPs were created as described previously (21). Briefly, two pairs of annealed oligonucleotides designed to restore the ADE2 coding sequence in plasmid pTW423 were ligated onto the ends of pTW423 digested with BglII and XhoI (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligonucleotide-modified Plasmids-OMPs were created as described previously (21). Briefly, two pairs of annealed oligonucleotides designed to restore the ADE2 coding sequence in plasmid pTW423 were ligated onto the ends of pTW423 digested with BglII and XhoI (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we sought to determine why only some joints that require gap filling are Pol4-dependent by using oligonucleotide-modified plasmids (OMPs) to perform a systematic analysis of DSB end configurations (21). We found that only NHEJ events that involve 3Ј-overhangs and require gap filling on both strands are strongly Pol4-dependent, with Pol4 promoting accurate repair.…”
mentioning
confidence: 99%
“…TdT is only expressed in early B-and T-lymphocytes, making it most relevant to the NHEJ repair that occurs during V(D)J recombination, where it has a major role in promoting immunoglobulin diversity. DNA polymerases outside the Pol X family are able to incorporate nucleotides during NHEJ, but only in a template-dependent manner (16,17,(57)(58)(59).…”
Section: The Polymerases Of Nhejmentioning
confidence: 99%
“…We suspect that broken chromosome ends were incompatible to simply join in all cases except one (subject 70; Gajecka et al 2006b). NHEJ is synonymous with the Ku-and DNA ligase IV-dependent rejoining mechanisms (Daley and Wilson 2005). Broken DNA strands in derivative chromosome formation must be aligned and, after nucleolytic processing of broken DNA ends, small gaps need to be filled prior to DNA joining.…”
Section: Nonhomologous End-joining Involvement In Translocation Formamentioning
confidence: 99%